Interpenetrating polymer networks of collagen, hyaluronic acid, and chondroitin sulfate as scaffolds for brain tissue engineering - Li, F; Ducker, M; Sun, B; Szele, FG; Czernuszka, JT (Elsevier, 2020)
Stem cells can provide neuro-protection and potentially neuro-replacement to patients suffering from traumatic brain injuries (TBI), with a practical option being delivery via engineered scaffolds. Collagen (Coll) and glycosaminoglycan (GAG) have been used as scaffolds for brain tissue engineering yet they often do not support cell differentiation and survival. In this study, we developed interpenetrating polymer network scaffolds comprising Coll, and incorporating two commonly found GAGs in the brain, chondroitin sulfate (CS) and/or hyaluronic acid (HA). We seeded these scaffolds with mouse neural stem cells from the subventricular zone (SVZ) niche. Compared to Coll-alone, all other substrates decreased the percent of nestin+ stem cells. Coll-CS-HA was more efficient at suppressing nestin expression than the other scaffolds; all SVZ cells lost nestin expression within 7 days of culture. In contrast to nestin, the percentage of microtubule associated protein 2 (MAP2+) neurons was greater in scaffolds containing, CS, HA or CS-HA, compared to Coll alone. Finally, Coll-CS increased the percentage of glial fibrillary acidic protein (GFAP+) astrocytes compared to Coll scaffolds. Overall, this work shows that Coll-HA and Coll-CS-HA scaffolds selectively enhance neurogenesis and may be advantageous in tissue engineering therapy for TBI.